Sound Documents, Biographical Resonances and Montage for the Configuration of Idiorrhythmic Constellations: - Denise Cobello (Revista Brasileira de Estudos da Presença, 2024)
Sound Documents, Biographical Resonances and Montage for the Configuration of Idiorrhythmic Constellations: the mutual influence between Lola Arias and Ulises Conti – This article explores the scenic and sonic dimensions of works resulting from the collaboration between director Lola Arias and composer Ulises Conti. Their partnership reflects an exploration of discursive universes as dynamic entities in continuous flux. We aim to map the creations that emerged from this collaboration and analyze key features of their works, focusing on the mutual influences at play. Drawing on the theories of Roland Barthes, we suggest that these creations configure idiorrhythmic constellations that merge personal narratives with collective experiences.